If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 5) + 3 = 38 Reorder the terms: 7(5 + x) + 3 = 38 (5 * 7 + x * 7) + 3 = 38 (35 + 7x) + 3 = 38 Reorder the terms: 35 + 3 + 7x = 38 Combine like terms: 35 + 3 = 38 38 + 7x = 38 Add '-38' to each side of the equation. 38 + -38 + 7x = 38 + -38 Combine like terms: 38 + -38 = 0 0 + 7x = 38 + -38 7x = 38 + -38 Combine like terms: 38 + -38 = 0 7x = 0 Solving 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '7'. x = 0 Simplifying x = 0
| d-2=14.9 | | 8a+2a=12 | | 15x-9=45x+3 | | -11+x=x+27 | | 4-2y=3(y-7) | | 0=15x^2+24x-32 | | -4y+2=-2(3y+5) | | -19x=-741 | | 22+3333= | | a^2+11ab+24b^2= | | 100.3=2.5b+6 | | ((3x-21)/(x+11))+8 | | 12t(t+m)(t-3m)=0 | | 65=20+.75d | | t^2-2t+4=0 | | 65=20+.75 | | e+13= | | x=4/23*(130-y) | | 6(x+2)-(13x+2)=1214 | | 5x-14=-2x | | x-1.9=3.1 | | 414cm= | | 5x-71=64-4x | | -7=2x+5x+7 | | 0=2X^2-3X-36 | | y(y+18)=-56 | | 45x-5=26y | | 6-4x=7x-9+10 | | 24a-22=-1(1-6a) | | y(y+2)=63 | | -12x^2y+8xy=0 | | (-12x^2)y+8xy=0 |